Association of subthreshold manic symptoms and cognitive impairments in euthymic patients with bipolar disorder I. (August 2019) - Zhang, Xiaofei; Cheng, Xiongchao; Chen, Jianshan; Zhang, Bin; Wu, Qiuxia; Deng, Wenhao; Li, Xuan; Lin, Yin; Yang, Chanjuan; Cao, Liping
Highlights: Subthreshold manic symptoms are an important problem in euthymic bipolar disorder. Remitted bipolar patients have impaired language, attention, and immediate memory. Providing adequate treatment is important to eliminate subthreshold symptoms. Abstract: Cognitive impairments exist during the euthymic period of bipolar disorder (BD). However, the impact of clinical factors (e.g., subthreshold symptoms and body mass index) on cognitive function in euthymic patients with bipolar disorder I is inconsistent. This cross-sectional study included 83 patients with euthymic BD I and 115 healthy controls. The Repeatable Battery for the Assessment of Neuropsychological Status indices were used to assess cognitive function. We assessed the relationship between cognitive function and clinical impact factors. Performance in language abilities, attention, and immediate memory was worse in euthymic BD I. Spearman's correlation revealed that indices for immediate memory and attention were negatively correlated with subthreshold manic symptoms, and indices for delayed memory were positively correlated with years of education. Linear regressions indicated that subthreshold manic symptoms were the best predictors of immediate memory and attention. Years of education predicted performance in most cognitive domains, except immediate memory. Individuals with euthymic BD I exhibited cognitive deficits in language learning, attention, and immediate memory. Our study highlights the importance of the effect of subthreshold manic symptoms on cognitive function in remitted BD; these symptoms should receive more attention and be targeted in personalized clinical therapeutic interventions.